Qazaf (False Accusation) in Malaysian Syariah Criminal Law: A Current Analysis: (Qazaf dalam Undang-undang Jenayah Syariah di Malaysia: Suatu Analisis Semasa) (Kanun: Jurnal Undang-undang Malaysia, 2018)
Qazaf (false accusation) is one of the crimes under the hudud category, for which the punishments are fixed in Islamic law, either through Al-Quran or As-Sunnah. In the context of implementation in Malaysia, the Federal Constitution generally places, qazaf offences under the jurisidiction of Syariah law as enforced by the states. Nevertheless, based on research on Syariah criminal law in the various states, it has been discovered that there is an apparent inconsistency in terms of the implementation surrounding qazaf offences. In fact, the states have different interpretations of the very definition of qazaf. Pursuant to this inconsistency, there is an alarming concern that the Syariah law may be seen in a negative light. This finding is further supported by the already-decided cases from the Syariah court. This article further proposes several recommendations to strengthen implementation in relation to enforcement concerning qazaf offences. This is to ensure that the legal provisions provided are meaningful, are appreciated by the community, and do not merely serve as a tool to fill in the present lacuna.Keywords: qazaf (false accusation), adultery, sodomy, Federal Constitution, syariah criminal law, syariah criminal law enactment